Axial beanspruchte K-Knoten aus dünnwandigen Rechteckhohlprofilen - Fleischer, Oliver (Berichte zum Stahl- und Leichtbau / Karlsruher Institut für Technologie, Versuchsanstalt für Stahl, Holz und Steine, Stahl- und Leichtbau, 2014)
Many of the sections included in the technical delivery conditions can only be used s by an acceptance for individual cases due to the limited application range of rectangular hollow section joints. The presented design approach allows for the design of K joints with thin-walled chord sections and makes these sections accessible to design. Additionally, it enables the design of joints with small gaps.